Exploration of Tax Research in The Era of COVID-19 - Bambang Soebroto; Ayu Fury Puspita; Made Tara Damayanti; Maria Inggried Soinia Lase; Muhammad Farras Mufid (AIBPM Publisher, 2023)
Indonesia's primary source of state revenue, which is the center of attention, has also been impacted by the Covid-19 virus. To support the revival of Indonesia's economy, the government has introduced Minister of Finance Regulation Number PMK-86/PMK.03/2020, which provides tax incentives for taxpayers who have been affected by the Covid-19 pandemic in 2019. The public, especially researchers, needs to understand the mechanism for compiling and developing research related to the latest issues in the field of taxation to produce quality research, which is the goal of implementing community service activities this time. The activity is carried out by presentation and discussion method. The material to be delivered includes the preparation of research and the development of research issues in the taxation field. The results showed that more than 60% of the participants felt helped by the socialization with this topic. The benefits of this activity are that participants understand the preparation and research methods and explore research ideas according to the latest issues and phenomena in the field of taxation.